MicroRNAs 221 and 222 regulate the undifferentiated state in mammalian male germ cells - Yang, Qi-En (Company of Biologists, 2013)
Continuity of cycling cell lineages relies on the activities of undifferentiated stem cell-containing subpopulations. Transition to a differentiating state must occur periodically in a fraction of the population to supply mature cells, coincident with maintenance of the undifferentiated state in others to sustain a foundational stem cell pool. At present, molecular mechanisms regulating these activities are poorly defined for most cell lineages. Spermatogenesis is a model process that is supported by an undifferentiated spermatogonial population and transition to a differentiating state involves attained expression of the KIT receptor. We found that impaired function of the X chromosome-clustered microRNAs 221 and 222 (miR-221/222) in mouse undifferentiated spermatogonia induces transition from a KIT(–) to a KIT(+) state and loss of stem cell capacity to regenerate spermatogenesis. Both Kit mRNA and KIT protein abundance are influenced by miR-221/222 function in spermatogonia. Growth factors that promote maintenance of undifferentiated spermatogonia upregulate miR-221/222 expression; whereas exposure to retinoic acid, an inducer of spermatogonial differentiation, downregulates miR-221/222 abundance. Furthermore, undifferentiated spermatogonia overexpressing miR-221/222 are resistant to retinoic acid-induced transition to a KIT(+) state and are incapable of differentiation in vivo. These findings indicate that miR-221/222 plays a crucial role in maintaining the undifferentiated state of mammalian spermatogonia through repression of KIT expression.